Borehole evidence for wing-like clastic intrusion complexes on the western Norwegian margin - Jackson,CAL; Somme,TO (Geological Society of London, 2011)
Data from a borehole on the Norwegian margin indicate that a strata-concordant amplitude anomaly within the Upper Cretaceous succession represents a 15 m thick sandbody that was either intruded in the subsurface or extruded on the palaeo-seabed. This observation implies that spatially related, strata-discordant anomalies are the seismic expression of sandstone dykes, thereby supporting previous geometry-based interpretations of the origin of these amplitude anomalies. Furthermore, this study indicates that thickness of an intrusion may be overestimated if based solely on seismic reflection mapping, and that this may lead to erroneous calculation of the ratio between depositional and intruded sandstone.